Analisis Pengaruh Ukuran Perusahaan Terhadap Audit Delay Berdasarkan Literature Review Terindeks Sinta - Kau, Sasmita Trimoelya; Santoso, Rachmat Agus; Fitriana, Fitriana (Universitas Gorontalo, 2024)
The purpose of preparing this literature review article is to find out and review previous research on the relationship between company size and audit delay. This research in preparing the article uses qualitative descriptive methods and literature studies to strengthen arguments through information collected from articles published in sinta indexed journals. The results of this study indicate that company size has no significant effect on audit delay, this is because those who cite more research other than company size and there are other variables that have a significant effect on audit delay. As well as from the 20 journals reviewed, only 8 journals state that company size has a significant effect on audit delay.